The politics of vaccination : practice and policy in England, Wales, Ireland, and Scotland, 1800-1874 - Brunton, Deborah (Rochester studies in medical history., 2008)
The introduction of public vaccination was among the greatest of public health triumphs. By the end of the nineteenth century, legislation framed and implemented by medical experts in Britain's government brought smallpox under control for the first time.